Synergistic effects of nutmeg and citrus peel extracts in imparting oxidative stability in meat balls. (April 2018) - Nishad, Jyoti; Koley, Tanmay Kumar; Varghese, Eldho; Kaur, Charanjit
Abstract: Nutmeg (NM) and citrus peel (CP) extracts are potential sources of phytochemicals high in antioxidant activity. The synergistic effect of the extracts when incorporated as a binary mixture (NM-CP) demonstrated high antioxidant activity, exceeding the expected values indicating possible interactive synergism. This effect prompted us to investigate the potential of NM, CP and NM-CP extracts in imparting oxidative stability to meat balls during frozen storage. NM-CP was evaluated at two concentrations 0.5% (NMCP) and 1.0% (NMCP1). Meat balls with added salt (MS) and control (without any salt and antioxidant) served as control. Binary mixture (NM-CP) at 1% showed a stronger inhibitory effect on lipid oxidation in comparison to the NMCP and individual extracts NM and CP. However, with respect to protein oxidation, both concentrations (NMCP and NMCP1) exhibited higher inhibitory activity than the individual counterparts. Color, flavor and sensory scores further confirmed the efficacy of NM-CP in extending the storage life of frozen meat. Synergistic effect of binary extract NMCP in retarding lipid and protein oxidation in meat balls could be of practical value for meat processors. Graphical abstract: Unlabelled Image Highlights: Citrus peel (CP) and nutmeg (NM) extracts used in frozen meatballs. Individual CP and NM extracts compared with binary (NM-CP) mixture. NM-CP was more effective than individual extracts in preventing oxidation. NM-CP showed a synergistic effect in preventing color change in meatballs. Chemometric analysis established the positive effects of binary extracts.